1986
DOI: 10.1073/pnas.83.24.9418
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an activated c-Ki-ras oncogene in rat liver tumors induced by aflatoxin B1.

Abstract: Weanling male Fischer rats were administered 40 intraperitoneal i tections of aflatoxin B1 (25 jug per animal per day) over a 2-month period. This chronic dosing regimen resulted in the sequential formation of hyperplastic foci, preneoplastic nodules, and hepatocellular carcinomas in all of the animals treated. The presence of transforming DNA sequences was detected by formation of anchorage-independent foci after transfection of tumor-derived DNA in NIH 3T3 mouse fibroblasts. Transfection of genomic DNA isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(41 citation statements)
references
References 36 publications
(30 reference statements)
1
39
1
Order By: Relevance
“…and N. Crawford, unpublished results). Other oncogenes, notably ras and raf, have been detected in some rat and mouse hepatomas induced with chemical carcinogens (25)(26)(27), but Reynolds et al (28) detected virtually no transforming genes in spontaneous hepatomas of F344 rats. One consistent finding, though, has been an elevation of c-myc transcripts in hepatocellular carcinomas (3)(4)(5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
“…and N. Crawford, unpublished results). Other oncogenes, notably ras and raf, have been detected in some rat and mouse hepatomas induced with chemical carcinogens (25)(26)(27), but Reynolds et al (28) detected virtually no transforming genes in spontaneous hepatomas of F344 rats. One consistent finding, though, has been an elevation of c-myc transcripts in hepatocellular carcinomas (3)(4)(5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
“…The treatment protocol used to induce tumors was essentially the same as in the previous experiment, except that carcinogen dosing was initiated at 36 rather than 21 days of age. As expected, this change in protocol resulted in a longer latency period for tumor development and, consequently, reduced the incidence of end-stage hepatocellular carcinomas at the time the experiment was terminated (68 weeks after termination of dosing), compared with similar studies involving treatment of younger animals (22). All liver tissues obtained from animals killed 63 weeks after termination of dosing and beyond showed morphological changes characteristic of malignant neoplasms (21).…”
Section: Discussionmentioning
confidence: 84%
“…Thus, examination of 4 activated fibrosarcomas induced in rats by 1,8-dinitropyrene (1, revealed that 1 tumor contained K-ras, while the other 3 contained activated genes that were unrelated to ras (70,71). In addition, McMahon et al (72) have provided evidence for transforming gene activation in a high proportion of hepatocellular carcinomas induced in Fischer rats by aflatoxin B1. Activated K-ras was detected in 2 carcinomas, while evidence that 8 of the 11 tumors contained genes that were unrelated to ras was also provided.…”
Section: Uncharacterized Transforming Genesmentioning
confidence: 99%